The Poetic image of Existence and its aesthetic manifestations in the philosophy of Nietzsche - Meree, Manal Ismail (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research in the Poetic of Existence and its aesthetic manifestations in the philosophy of Nietzsche aims to clarify an essential idea which is that the existence. we live in doesn’t have a single human facet or interpretation, but holds many. Therefore to explain this existence only by science or mind will be unfair to our lives, world, and existence. For science only represents one facet of humanity, and every vision represents its own particular perspective, so the picture will be complete only if we combine as much of these vision and perspectives as possible, we won’t say all but at least the minimum.Thus opening the horizon to a deeper view of humanity, its title is the art.Which will restore the social balance between science, mind, religion and morality, and will make man achieve humanity in his world and land. This achievement,which has not yet been complete due to the role of metaphysical concepts of all kinds, and their strong echoes through history, of making man lose his true values.